Comparative study of National Institute of Health criteria and TNM staging system in predicting the prognosis of gastrointestinal stromal tumours: a retrospective study - Chen, Jin-hu; Yang, Zhen-rong; Cai, Zhi-ming; Lin, Tao; Lin, Ren; Su, Xin-cheng; Kang, Rong-bin; Lin, Lu; Ye, Zai-sheng; Zhou, Yong-jian (Frontiers in Oncology, 2025)
BackgroundIn 2009, the American Joint Commission on Cancer incorporated the gastrointestinal stromal tumours (GISTs) risk classification into the tumour, node, metastasis (TNM) staging system. We aimed to evaluate the prognostic value of the TNM staging system for GISTs by directly comparing it with the modified National Institutes of Health (NIH) criteria.Materials and methodsWe /used data from the Surveillance, Epidemiology, and End Results (SEER) database (2010–2019) to retrospectively analyse patients with gastric and small intestinal/colorectal GISTs. Multivariate Cox regression analysis was performed to identify independent prognostic factors for cancer-specific survival (CSS). To assess the predictive performance of the TNM staging system and the modified NIH criteria, we calculated the area under the receiver operating characteristic curve (AUC), concordance index (C-index), Akaike information criterion (AIC), and Bayesian information criterion (BIC).ResultsOf the 3,034 patients included, 2,106 had gastric GISTs and 928 had small intestinal/colorectal GISTs. Multivariate Cox analysis revealed that TNM stage was an independent prognostic factor for CSS. According to the modified NIH criteria, both the overall and subgroup cohorts exhibited better CSS in the low-risk group than that in the very low-risk group. In contrast, for the TNM staging system, the difference in CSS between stages IIIA and IIIB were not statistically significant (all P>0.05). Notably, only 2 of the 928 patients with small intestinal/colorectal GISTs met the modified NIH criteria for intermediate risk. In the gastric GISTs cohort, the AUC, C-index, AIC, and BIC values for the TNM staging system and the modified NIH criteria were similar. However, in the small intestine and colorectal GISTs cohort, the TNM staging system demonstrated better discriminatory performance with higher AUC and C-index and lower AIC and BIC values compared with the modified NIH criteria.ConclusionsRegarding prognostic evaluation, the TNM staging system was comparable to the modified NIH criteria for patients with gastric GISTs, but it outperformed the modified NIH criteria in the prediction of outcomes for patients with small intestine and colorectal GISTs.